Integrating Augmented Reality (AR) and Artificial Intelligence (AI) Based Learning Media in Early Childhood English Language Introduction - Siswono, Hendrik; Zahro, Ianatuz Zahro (Journal of Education Technology and Inovation, 2025)
This study aims to explore the development and effectiveness of English learning media for early childhood through the integration of Augmented Reality (AR) and Artificial Intelligence (AI). The background of the research lies in the increasing demand for innovative and interactive learning tools that can support vocabulary acquisition and pronunciation practice in young learners. Employing the ADDIE instructional design model, the research followed five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed media incorporated 3D AR visuals and an AI-powered speech recognition system for real-time pronunciation feedback. Data were collected through expert validation, pre-test and post-test assessments, as well as observation and teacher interviews. Results showed a significant improvement in children's vocabulary mastery and speaking confidence, with post-test scores increasing by over 38%. Furthermore, students exhibited high engagement and autonomy during learning sessions. The integration of AR and AI proved to be both pedagogically effective and developmentally appropriate. In conclusion, this research confirms that AR and AI-based media are valuable tools for enhancing English learning among young children, offering interactive, personalized, and immersive learning experiences that support 21st-century educational goals